Molecular photophysics and spectroscopy - Andrews, David L., 1952-; Lipson, R. H. 1955- (IOP Publishing, 2021)
This new, expanded edition provides a fresh, photon-based description of modern molecular spectroscopy and photophysics, with applications that are drawn from across the breadth of chemistry, biology, physics, and materials science, including recent developments. The focus is on the mechanisms that operate at the fundamental level, on how light absorption and scattering occur in molecules, what happens to the energy which the molecules acquire, and what may be learned from the study of these processes. Mathematics is again kept to a minimum though quantitative understanding is nevertheless put into practice via example calculations throughout the text. With the aid of extensive, purposely devised illustrations, this approach fosters a deeper intuition for the photophysical processes involved in light matter interaction, aiming to consolidate the principles and to exemplify how widely ranging information can be derived from spectroscopic studies.- Resumé vydavatel